Context-Driven Creative Workshop: Celebrating Locality in Disaster-Affected Communities - Purnasasmita, Ruth Kartika; Paramita, Kristanti Dewi; Atmodiwirjo, Paramita (UI Scholars Hub, 2024)
This paper explores the idea of context as the basis for developing creative workshops for children in disaster-stricken communities. We argue that creative learning should not be seen merely in terms of artistic expression and abstract thinking. Instead, it should become a platform for celebrating local contexts and cultures through the learning process. This study was based on reflecting on two creative workshop activities that were held in post-disaster schools in Cianjur, West Java. The school is part of the Sekolah Indonesia Cepat Tanggap (SICT) program—a fast-track school construction initiative for communities affected by disasters throughout Indonesia. The creative workshops were conducted to engage and familiarize students with their new school environments and build their sense of ownership of their new schools based on the idea that creative workshops for communities can be informed by the richness of local food, agriculture, local events, and experiences in context. This contextual information was embedded in the workshops, enabling the children to produce creative works that highlighted individual and collective layers of locality. The relationship between the creative media used in the workshops and the context allowed the students to produce works that freely expressed their identities, reflecting their belongingness and roles within society. The students’ work was later exhibited in the schools, enabling them to interactively engage with the school spaces. This article outlines context-based learning strategies that can be used in creative workshops to enable communities to situate and express aspects of their everyday localities.